Myositis ossificans traumatica of the medial pterygoid muscle: a case report. - Trautmann, Fernanda; Moura, Paula de; Fernandes, Tito L; Gondak, Rogério O; Castilho, Julio C de M; Filho, Edmundo Medici (My University, 2010)
In this report, we present a case of myositis ossificans traumatica (MOT) of the medial pterygoid muscle that had developed after mandibular block anesthesia administered for endodontic treatment of the lower right second molar, demonstrating typical features of this condition. MOT should be considered as a differential diagnosis when there is severe limitation of jaw opening and an associated trauma. Panoramic radiographs and axial and coronal computed tomography (CT) scans can effectively delineate the calcified mass. Other imaging studies that may be helpful include magnetic resonance imaging (MRI), bone scans, and ultrasound. As shown in our case, calcified masses were found in the right mandibular angle, which severely limited jaw opening. Some earlier reported cases of MOT were treated by extraoral surgical approaches with complete removal of the evolving muscle. The aim of this case report is to present only the diagnostic imaging aspects of myositis ossificans traumatica.
Keywords: adult; case report; cone beam computed tomography; differential diagnosis; human; injury; joint characteristics and functions; male; masticatory muscle; ossifying myositis; pathology; radiography; soft tissue injury; Adult; Cone-Beam Computed Tomography; Diagnosis, Differential; Humans; Male; Myositis Ossificans; Pterygoid Muscles; Range of Motion, Articular; Soft Tissue Injuries